ANALISIS PENGARUH DEBT DEFAULT, KUALITAS AUDIT, OPINION SHOPPING DAN KEPEMILIKAN PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Muhammad Jauhan Irfana; Dul Muid (Diponegoro Journal of Accounting, 2012)
This study aims to analyze and provide empirical evidence of the influence of debt defaul, quality audit, opinion shopping, ownership of companies (managerial ownership and institutional ownership on the probability of receiving a going concern opinion. Hypothesis proposed (1) debt default affect the probability of accepting the going concern opinion, (2) audit quality effect on reception going concern opinion, (3) opinion shopping influence the acceptance of going concern audit opinion, (4) managerial ownership affect the acceptance of going concern audit opinion, (5) istitusional ownership affect the acceptance of going concern audit opinion . This study used 25 manufacturing companies listed on the Stock Exchange 2008-2010. Data was collected by using a purposive sampling method towards manufacturing companies listed in the Indonesia Stock Exchange. The research data were analyzed with logistic regression analysis. The results, based on logistic regression analyses, indicated that debt default, audit quality and managerial ownership has no effect on revenues going concern opinion. While the opinion shopping and institutional ownership affects the revenue going concern audit opinion.